THE ROLE OF RELIGION LECTURERS IN PREVENTING RADICALISM AT PUBLIC UNIVERSITIES - Rohmatul Faizah; Ahmad Baedowi; Cholid Fadil (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2021)
This study aims to determine how the development of understanding of UPN Veterans East Java lecturers and students about radical movements in the campus environment. This type of research is qualitative research with a phenomenological approach involving a lecturer of Religion at UPN Veteran East Java as the research subject. From the results of the interviews, it was found that the lecturers had the same view on radicalism. This radicalism understanding develops from a lack of in-depth religious understanding. Meanwhile, among students, the development is due to the immaturity of students' thinking patterns and their great curiosity. The role of Religion lecturers in preventing radicalism at UPN Veterans East Java is by instilling the spirit of nationalism based on the Unitary State Republic of Indonesia, Pancasila, and the 1945 Constitution, defending the state to students, teaching Islamic insights that are Rahmatan Lil Alamin, moderate, open, and tolerant, fostering Islamic brotherhood, ukhuwah wathaniyah, and ukhuwah basyariah as well as instilling critical thinking in students.Keywords: The Role of Religion Lecturers, Preventing Radicalism